SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENERIMA REWARD SISWA BEPRESTASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI PONDOK PESANTREN DARUL QUR’ÁN GUNUNGKIDUL YOGYAKARTA - Yusron -; Muhammad Sholeh; Uning Lestari (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
Giving outstanding studentreward at Darul Qur'an Boarding School is one of the institution's efforts to improve student’s motivation to follow the activitieslearning. In the determination of the recipient of the reward is often encountered obstacles or problems, one of which is how to determine the students who deserve rewards, while this way is used only subjective judgments so less efficient. In order to make the assessment of the students more objective, the agency wants the application to assess the students of some predetermined criteria. This research uses SAW (Simple Additive Weighting) method. SAW weighted sums, ie, by searching for the weighted sum of the performance values ​​of each alternative, across all attributes and requiring the process of normalizing the decision matrix (X) to a scale comparable to all available alternative values. The result of decision support system (DSS) application of reward recipient can assist the student in determining the achievement of the recipient of the reward, so that in the process of distribution can be submitted to the students who really deserves, so that the distribution can be on target. Assessment results are displayed based on the largest or smallest value, making it easier for decision makers to choose the best alternative from a number of alternatives.